The MEK Inhibitor Trametinib Suppresses Major Histocompatibility Antigen-mismatched Rejection Following Pancreatic Islet Transplantation. Issue 9 (September 2020) - Tada, Seiichiro; Anazawa, Takayuki; Shindo, Takero; Yamane, Kei; Inoguchi, Kenta; Fujimoto, Nanae; Nagai, Kazuyuki; Masui, Toshihiko; Okajima, Hideaki; Takaori, Kyoichi; Sumi, Shoichiro; Uemoto, Shinji
Abstract : Background: Potential adverse effects, such as functional impairment of islets, render conventional immunosuppressive drugs unsuitable for use in islet transplantation. In addition, as a single therapy, they cannot prolong islet allograft survival. Here, we investigated the utility of the mitogen-activated protein kinase inhibitor trametinib and asked whether it ameliorates acute rejection of transplanted islets without the need for conventional immunosuppressants. Methods: Islets from fully major histocompatibility complex-mismatched BALB/c mice were transplanted into streptozotocin-induced diabetic C57BL/6 mice via the portal vein. These mice received trametinib or vehicle (orally) for 28 days. Isolated islets from BALB/c mice were incubated in vitro with different concentrations of trametinib to determine viability and function. Results: Trametinib (0.1 and 0.3 mg/kg) prolonged graft survival significantly ( P  = 0.0007 and P  = 0.005, respectively) when compared with vehicle. Histologic analyses revealed that cellular infiltration of the graft by lymphocytes was inhibited significantly on day 7 ( P  < 0.05). In addition, trametinib suppressed functional differentiation of naive CD4 + T cells in recipients. Expression of mRNA encoding inflammatory cytokines interleukin (IL)-2, tumor necrosis factor α, and interferon γ in recipients treated with trametinib was also inhibited ( P  < 0.001, P  < 0.05, and P  < 0.01, respectively). Trametinib also increased production of IL-4 and IL-10 ( P  < 0.05 and P  = 0.20, respectively). In vitro, islets incubated with different concentrations of trametinib exhibited no harmful effects with respect to viability and function. Conclusions: Trametinib delayed islet graft rejection by inhibiting functional differentiation of naive CD4 + T cells and regulating inflammatory cytokines. Trametinib might be a promising candidate for maintenance immunosuppressive therapy after allogeneic islet transplantation.